Serum Klotho levels and epilepsy among U.S. adults in the NHANES 2013–2016: a cross-sectional study - Chen, Minghong; Chen, Junyu; Wang, Xuerui; Long, Tianyi (Scientific reports, 2025)
The relationship between Klotho and epilepsy is poorly understood. This study aimed to investigate the association between serum Klotho levels and epilepsy. A total of 99,966 individuals who participated in the NHANES from the 2013 to 2016 were initially included. After excluding participants with missing data on serum Klotho concentration (57,286), epilepsy (6) and relevant covariates (6,096), the final sample consisted of 36,578 participants, with a mean age of 59 years. Weighted multivariable logistic regression analyses showed that high serum Klotho levels were negatively associated with the prevalence of epilepsy, with an odds ratio (OR) of 0.74 (95% confidence interval [CI]: 0.64 to 0.86; P < 0.001. The Restricted Cubic Spline analyses (RCS) model showed a non-linear relationship between the serum Klotho levels and epilepsy. Subgroup analysis showed that serum Klotho levels were negatively correlated with epilepsy prevalence in individuals under 65 years of age and in males. Our study suggests that serum Klotho levels were associated with the prevalence of epilepsy. Further large-scale prospective studies and randomized trials are warranted to confirm our findings.